An Alternative Method for Evaluation of Resistance to Low ph and Bile Salts in Probiotic Characterization of Lactobacillus Reuteri Strains. A Technical Note - Bolado-Martínez, Enrique; Pérez-Morales, Rosalva; Acedo-Félix, Evelia (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
A considerable amount of attention has been focused on the use of lactobacilli as probiotics. The use of microorganisms as probiotics must meet certain criteria, among these; the resistance to low pH and bile salts is of great importance. Different procedures have been designed to evaluate tolerance to gastrointestinal transit. Since resistance to low pH and bile salts is critical in the evaluation of probiotic strains, the aim of this study was to compare resistance to bile salts for 20 strains of porcine Lactobacillus reuteri that had been isolated from healthy pigs, using two different procedures based on exposure to low pH. Statistical analysis revealed no difference in resistance of the strains to bile salts whether pH was low or not. The use of low pH prior to exposure to bile salts therefore more closely represents physiological conditions that should be used for the evaluation of potential porcine probiotic lactobacilli. Further studies using digestive enzymes are required to evaluate resistance to gastrointestinal transit, since it is an important factor in the evaluation of strains with potential probiotic activity